Focus-Group Regarding the Psycho-Pedagogical Effects Felt by Children as a Result of the Parents’ Migration - Disca, Tiberiu (European Journal of Social Science Education and Research, 2023)
The focus group method is a qualitative method which requires as technique the interview with a work group and a moderator. It is a research structure with scientific, social or public opinion commercial aim. In preparing the focus group I have determined the topic of the discussions based on an interviewing guide and I have determined the correspondence of the groups. Therefore, there had been five focus-groups, the discussions had a length of 75-90 min, recorded in an audio format, after receiving the subjects’ permission. There were 5 focus-groups: focus-group 1: parents that have experienced first-hand migration but have returned back (7 men and 3 women); focus-group 2: parents/grandparents of the children with a migrant parent, enrolled at a Step-by-step or After school program (7 women and 4 men); focus-group 3: primary school teachers, school counsellors of the students with at least one migrant parent (9 primary school teachers, 2 counsellors); focus-group 4: parents/grandparents that have in their care at least one child after the migration of the parent(s) abroad (3 men, 7 women or 4 parents and 6 grandparents); focus-group 5: 10 school counsellors (psychologists) of the schools from the surroundings of Hunedoara (including Calan town and Pestis, Teliuc and Ghelari villages). In conclusions, the migration of a parent brings negative effects over the psycho-pedagogical evolution of the kid; all followed indicators have had negative effects after the migration, with the exception of the one that speaks about life conditions. Whether they have or not passed through an experience of migration, all subjects have affirmed that the absence of a parent or both has repercussions over the normal development of the child.